Digital Trust and Cooperation with an Integrative Digital Social Contract - Levine, Livia (Journal of business ethics, 2019)
I argue for the role of trust and cooperation as part of the foundation of digital commerce by expanding the reach of the Integrative Social Contract Theory (ISCT) of Donaldson and Dunfee (Ties that Bind, 1999). I propose that a digital business community can be a community in the morally relevant ways that Donaldson and Dunfee describe, and that the basic framework of ISCT can apply to the digital business world similarly to its application in the offline business world. I then analyze the roles of trust and cooperation in e-commerce, showing how they are important to the digital business community and explaining their moral relevance under a digital form of ISCT. I use the ISCT framework to show that trust and cooperation are an instantiation of the hypernorm of necessary social efficiency, and that authentic microsocial norms developed for the ends of trust and cooperation carry moral responsibility.